Melanocytes as emerging key players in niche regulation of limbal epithelial stem cells - Polisetti, Naresh; Gießl, Andreas; Zenkel, Matthias; Heger, Lukas; Dudziak, Diana; Naschberger, Elisabeth; Stich, Lena; Steinkasserer, Alexander; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula (Ocular Surface, 2021)
Purpose: Limbal melanocytes (LMel) represent essential components of the corneal epithelial stem cell niche and are known to protect limbal epithelial stem/progenitor cells (LEPCs) from UV damage by transfer of melanosomes. Here, we explored additional functional roles for LMel in niche homeostasis, immune regulation and angiostasis. Methods: Human corneoscleral tissues were morphologically analyzed in normal, inflammatory and wound healing conditions. The effects of LMel on LEPCs were analyzed in direct and indirect co-culture models using electron microscopy, immunocytochemistry, qRT-PCR, Western blotting and functional assays; limbal mesenchymal stromal cells and murine embryonic 3T3 fibroblasts served as controls. The immunophenotype of LMel was assessed by flow cytometry before and after interferon-γ stimulation, and their immunomodulatory properties were analyzed by mixed lymphocytes reaction, monocyte adhesion assays and cytometric bead arrays. Their angiostatic effects on human umbilical cord endothelial cells (HUVECs) were evaluated by proliferation, migration, and tube formation assays. Results: LMel and LEPCs formed structural units in the human limbal stem cell niche in situ, which could be functionally replicated, including melanosome transfer, by co-cultivation in vitro. LMel supported LEPCs during clonal expansion and during epithelial wound healing by stimulating proliferation and migration, and suppressed their differentiation through direct contact and paracrine effects. Under inflammatory conditions, LMel were increased in numbers and upregulated expression of ICAM-1 and MHC II molecules (HLA-DR), but lacked expression of HLA-G, -DP, -DQ and costimulatory molecules CD80 and CD86. They were also found to be potent suppressors of alloreactive T- cell proliferation and cytokine secretion, which largely depended on direct cell-cell interaction. Moreover, the LMel secretome exerted angiostatic activity by inhibiting vascular endothelial cell proliferation and capillary network formation. Conclusion: These findings suggest that LMel are not only professional melanin-producing cells, but exert various non-canonical functions in limbal niche homeostasis by regulating LEPC maintenance, immune responses, and angiostasis. Their potent regulatory, immunomodulatory and anti-angiogenic properties may have important implications for future regenerative cell therapies.
CRIS-Team Scopus Importer:2021-09-03
Keywords: Angiostasis; Immune regulation; Inflammation; Limbal niche; Limbal stem cells; Melanocytes; Wound healing